(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to show the repercussions of the war in Syria on the agricultural sector in the Syrian coast. The study relied on the historical method, and the researcher followed the descriptive approach, which depends on collecting data and information that help in an accurate description of the problem, and analyzing it to reach accurate results. The study reached a set of results, including: The war has a direct and negative impact on all Syrian economic sectors, especially the agricultural sector, as it resulted in increased desertification and insufficient exploitation of rainwater, limited markets for Syrian agricultural products, and failure to exploit the relative advantages enjoyed by agriculture. Syrian agricultural exports are limited compared to what is possible, and the lack of clear mechanisms to deal with disasters, climate change and natural disasters that affect farmers. The researcher recommends the need to direct agricultural production to respond to the needs and requirements of local and foreign markets in terms of quality and price, which constitutes a major challenge that must be achieved, and work to control the quality, safety and conformity of agricultural products and live animals entering Syria, and implement interventions and procedures to provide additional water for agriculture and increase the agricultural area Through the reclamation and development of lands and the provision of additional or new financial sources for some lands that are not currently being used.